2017
DOI: 10.1111/nbu.12280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density: Applying behavioural science to weight management

Abstract: Studies conducted by behavioural scientists show that energy density (kcal/g) provides effective guidance for healthy food choices to control intake and promote satiety. Energy density depends upon a number of dietary components, especially water (0 kcal/g) and fat (9 kcal/g). Increasing the proportion of water or water-rich ingredients, such as vegetables or fruit, lowers a food’s energy density. A number of studies show that when the energy density of the diet is reduced, both adults and children spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 60 publications
1
71
0
8
Order By: Relevance
“…Home-made and industrial foods were found to have medium (12•6 kJ/g) and high (18•0 kJ/g) mean energy density, respectively (29) , which corroborates previous findings that street foods are energy-dense sources of nutrients for populations worldwide (10) . Industrial wafers and biscuits presented the highest energy density (approximately 20•9 kJ/g), possibly reflecting a high sugar and fat content (30) , as previously observed in samples of street food in Dushanbe, Tajikistan (26) .…”
Section: Discussionsupporting
confidence: 88%
“…Home-made and industrial foods were found to have medium (12•6 kJ/g) and high (18•0 kJ/g) mean energy density, respectively (29) , which corroborates previous findings that street foods are energy-dense sources of nutrients for populations worldwide (10) . Industrial wafers and biscuits presented the highest energy density (approximately 20•9 kJ/g), possibly reflecting a high sugar and fat content (30) , as previously observed in samples of street food in Dushanbe, Tajikistan (26) .…”
Section: Discussionsupporting
confidence: 88%
“…the calories provided per gram), which is typically the result of the fibre and/or water content of the food, it is possible to consume larger overall quantities of foods (on a volume or gram basis), making it far easier to achieve nutrient requirements within calorie requirements, provided the foods chosen are rich in essential nutrients. Furthermore, there is some evidence that the larger volume of food may help to reduce hunger between meals, which could aid weight loss (Rolls ). BNF’s Quality Calorie concept illustrates that the nutritional quality of food choices, even when calorie content remains the same, can vary considerably (BNF ).…”
Section: Good Nutrition Is More Than Reduced Calories and Sugarsmentioning
confidence: 99%
“…; Stelmach‐Mardas et al . ) and promote satiety (Rolls ), although the efficacy of this approach to support long‐term weight loss maintenance is unclear (Karl & Roberts ).…”
Section: The Slimming World Programmementioning
confidence: 99%
“…The Slimming World dietary approach (Food Optimising R ) encourages ad libitum intake of many lower energy-dense foods and controlled amounts of higher energy-dense foods. Research suggests that dietary approaches based on the promotion of lower energy-dense foods can reduce bodyweight (Rouhani et al 2016;Stelmach-Mardas et al 2016) and promote satiety (Rolls 2017), although the efficacy of this approach to support long-term weight loss maintenance is unclear (Karl & Roberts 2014).…”
Section: The Slimming World Programmementioning
confidence: 99%